Does postactivation potentiation (PAP) increase voluntary performance? - Zimmermann, H. B.; MacIntosh, B. R.; Dal Pupo, J. (Applied Physiology, Nutrition, and Metabolism, 2020)
The transient increase in torque of an electrically evoked twitch following a voluntary contraction is called postactivation potentiation (PAP). Phosphorylation of myosin regulatory light chains is the most accepted mechanism explaining the enhanced electrically evoked twitch torque. While many authors attribute voluntary postactivation performance enhancement (PAPE) to the positive effects of PAP, few actually confirmed that contraction was indeed potentiated using electrical stimulation (twitch response) at the time that PAPE was measured. Thus, this review aims to investigate if increases in voluntary performance after a conditioning contraction (CC) are related to the PAP phenomenon. For this, studies that confirmed the presence of PAP through an evoked response after a voluntary CC and concurrently evaluated PAPE were reviewed. Some studies reported increases in PAPE when PAP reaches extremely high values. However, PAPE has also been reported when PAP was not present, and unchanged/diminished performance has been identified when PAP was present. This range of observations demonstrates that mechanisms of PAPE are different from mechanisms of PAP. These mechanisms of PAPE still need to be understood and those studying PAPE should not assume that regulatory light chain phosphorylation is the mechanism for such enhanced voluntary performance.